Online search interest in the use of antibiotics for dental pain: an infodemiology study - Roxo-Gonçalves , Michelle; Valentim Bitencourt, Fernando; Britto Azevedo , Claudia; Fiorini , Tiago; Coelho Carrard , Vinicius (Brazilian Dental Science, 2022)
Objective: The objective of this study was to evaluate the online search interest pertaining to queries regarding antibiotics for dental pain. Material and Methods: Google Trends™ was used to identify the online search interest. Previously, a literature search was performed on the most frequently used antibiotics in dentistry in Brazil. Accordingly, the search terms used were Amoxicillin (AM), Clindamycin (CD), Azithromycin (AZ) and Metronidazole (MD), with the phrase “for toothache” in Portuguese and English. A time-series covered the last 240 weeks (from 2015 to 2020), and the results of each term were compared to their respective annual value. Geographic regions were also evaluated. To obtain a relative search volume (RSV), the resulting Google Trends™ numbers were then scaled to a range from 0 to 100 based on the ratio of searches on a topic to searches across all topics. Results: We observed an upward trend in all antibiotics search terms over the 5 years analyzed, with a peak of greater interest in 2019. The antibiotic of most interest related to toothache was ‘AM’, followed by ‘AZ’, ‘MD’, and ‘CD’. The annual RSV of toothache searches rose steadily from 2015 to 2020. Variations were observed between Brazilian geographic regions, and the Northeast region presented with the greatest interest in the topic. Conclusion: Although there were variations in annual and regional trends, an expressive and persistent increase in collective interest regarding the use of antibiotics related to toothache, mainly amoxicillin, was observed. Our findings provide insights for public health promotion programs. KEYWORDS Antibiotics; Internet; Community pharmacies; Oral health; Public health.